Oxytetracycline and penicillin-G residues in cattle slaughtered in south-western Nigeria: Implications for livestock disease management and public health (2013)
After the discovery of indiscriminate antibiotic use in ready-for-slaughter cattle in south-western Nigeria, 90 tissue samples from randomly selected slaughtered cattle were evaluated for oxytetracycline and penicillin-G residues using high performance liquid chromatography and the data analysed by one-way Analysis of variance (ANOVA). The findings revealed residues of oxytetracycline (kidney: 9.47 μ/kg ± 3.24 μ/kg; liver: 12.73 μ/kg ± 4.39 μ/kg; muscle: 16.17 μ/kg ± 5.52 μ/kg) and penicillin-G (kidney: 6.27 μ/kg ± 2.46 μ/kg; liver: 8.5  μ/kg ± 2.80 μ/kg; muscle: 11.67 μ/kg ± 2.94 μ/kg) in all tissues screened. Significantly high levels (oxytetracycline: F =  16.77; penicillin-G: F = 29.38) were, however, found in muscles, followed by liver and then kidney – findings confirming recent antibiotic administration to the animals before slaughter. The dietary intakes through the tissues screened were 0.024% (oxytetracycline) and 0.017% (penicillin-G) of the acceptable daily intake (ADI). Although the concentrations in the tissues screened were below the maximum residue limits despite recent administration of these antibiotics before slaughter, the lower concentrations are suggestive of the probable low dosages often administered by those involved in indiscriminate use of antibiotics. This therefore raises serious concerns for the livestock industry as well as human health, given the resultant emergence and spread of resistant strains of bacterial pathogens that could ensue from prolonged use of low dosages of antibiotics. Additionally, the lower concentrations of the daily intakes notwithstanding, the plausible exposure to these antibiotics from other food sources is a cause for concern. Since antimicrobial misuse and its consequent effects are not just a problem limited to Nigeria but also a concern in sub-Saharan Africa, the need for national and international stakeholder intervention is emphasised.